(+)-Usnic Acid and Its Derivatives as Inhibitors of a Wide Spectrum of SARS-CoV-2 Viruses - Filimonov, Aleksandr S.; Yarovaya, Olga I.; Zaykovskaya, Anna V.; Rudometova, Nadezda B.; Shcherbakov, Dmitriy N.; Chirkova, Varvara Yu; Baev, Dmitry S.; Borisevich, Sophia S.; Luzina, Olga A.; Pyankov, Oleg V.; Maksyutov, Rinat A.; Salakhutdinov, Nariman F. (Viruses, 2022)
In order to test the antiviral activity, a series of usnic acid derivatives were synthesized, including new, previously undescribed compounds. The activity of the derivatives against three strains of SARS-CoV-2 virus was studied. To understand the mechanism of antiviral action, the inhibitory activity of the main protease of SARS-CoV-2 virus was studied using the developed model as well as the antiviral activity against the pseudoviral system with glycoprotein S of SARS-CoV-2 virus on its surface. It was shown that usnic acid exhibits activity against three strains of SARS-CoV-2 virus: Wuhan, Delta, and Omicron. Compounds 10 and 13 also showed high activity against the three strains. The performed biological studies and molecular modeling allowed us to assume that the derivatives of usnic acid bind in the N-terminal domain of the surface glycoprotein S at the binding site of the hemoglobin decay metabolite.